Hermite-Hadamard type inequalities for functions whose n^th order of derivatives are s-convex in the second sense - Meftah, Badreddine; Merad, Meriem (Revista MATUA, 2017)
In this paper, we establish some Hermite-Hadamard type inequalities for functions whose n^th dirivatives are s-convex in the second sense. Several known results are derived . Applications to special means are also given.